2018
DOI: 10.4037/ajcc2018968
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Moral Distress in a US Sample of Critical Care Nurses

Abstract: 59Background Moral distress in registered nurses causes decreased job satisfaction, turnover in staffing, burnout, and heightened states of psychological distress. To date, investigation of modifiable factors, such as perceptions of the practice environment and patient safety, among a diverse sample of critical care nurses has been limited. Objective To explore the relationships among the severity of moral distress, the practice environment, and patient safety in a national sample of critical care nurses. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 24 publications
4
83
1
9
Order By: Relevance
“…The potential benefits of this constructive response to moral distress have been demonstrated where critical care nurses who reported a healthy practice environment with a culture of quality care had lower levels of moral distress. 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential benefits of this constructive response to moral distress have been demonstrated where critical care nurses who reported a healthy practice environment with a culture of quality care had lower levels of moral distress. 35…”
Section: Discussionmentioning
confidence: 99%
“…24,34 The potential benefits of this constructive response to moral distress have been demonstrated where critical care nurses who reported a healthy practice environment with a culture of quality care had lower levels of moral distress. 35 Also addressing work/team culture, Wocial et al 36 reported an intervention in which weekly rounds, collaboratively lead by a senior intensivist and a clinical ethicist, provided an opportunity for front line providers to discuss long-stay patients (> 10 days in a year); they found that the impact of these rounds markedly reduced mean moral distress scores and provided a positive platform for productive discussion of complex issues like goals of care. Similarly, Asgari et al 37 described a correlation between ethical climate and job satisfaction among critical care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…23 For critical care nurses, practice environment has been associated with moral distress; for example, nurses working in critical care units that have received the American Association of Critical-Care Nurses Beacon Award for Excellence for providing quality, evidence-based care in a collegial environment experienced less moral distress. 24 Social work-led reflective debriefing, mindfulness-based stress reduction, moral empowerment programs, and supportive ethical climate are also associated with lower moral distress among critical care nurses. [25][26][27] Physician trainees have reported that being notified of and discussing patient deaths and participating in death rounds helped them cope with moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…PICU staff have increased risk for moral distress due to the stressful environment, life-sustaining equipment, conflict over treatment, and futile family preferences. 2,3 Stress in the PICU leads to anxiety, burnout, and decreased job satisfaction. 4 Moral distress is a strong indicator of a nurse's intent to leave their job, with up to 25% of nurses leaving high-intensity work settings due to distress.…”
Section: Literature Synthesismentioning
confidence: 99%
“…One example is the pediatric intensive care unit (PICU) staff who experience increased risk for moral distress due to the demanding work environment. 1 , 2 , 3 , 4 Resilience, a protection against burnout, is the ability to positively respond to aversity. 5 Following a particularly difficult season, the nursing director heard from a staff nurse, “We have so many bundles to protect our patients; why don’t we have bundles to protect our staff?” This conversation prompted the successful creation of the resiliency bundle.…”
mentioning
confidence: 99%